Antarctic regional snow accumulation composites over the past 1000 years - Thomas, Elizabeth (Polar Data Centre, Natural Environment Research Council, UK, 2017)
Seventy-nine Antarctic ice core snow accumulation records were gathered as part of a community led project coordinated by the PAGES Antarctica 2k working group. Individual ice core records (kg m2 yr-1) were normalised relative to a reference period (1960-1990). The normalised records were separated into seven geographical regions and averaged together to form the regional composites. The seven geographical regions are: East Antarctica; Wilkes Land Coast; Weddell Sea Coast; Antarctic Peninsula; West Antarctic Ice Sheet; Victoria Land; and Dronning Maud Land. Full data description and methods can be found in Thomas et al., 2017. This record also includes the original data, from which the composite records were produced. This dataset represents an updated version of another published dataset. The update was necessary due to erroneous data contained in the files. Please use this corrected dataset in preference to the other one.